THE CHARACTERISTICS OF NANOPARTICLE QUALITY OF SAND SEA CUCUMBER (Holothuria scabra) MEAT COLLAGEN WITH DIFFERENT STIRRING TIME - Syafrijal Syafrijal; Sumarto Sumarto; Dewita Dewita (Berkala Perikanan Terubuk, 2018)
This research was aimed to determine the characteristics of nanoparticle quality of sand sea cucumber meat collagen (Holothuria scabra) with different stirring time. The method was carried out experimentally by conducting an experiment on nanoparticles of meat sand sea cucumber (Holothuria scabra) with different stirring i.e. 1, 2 and 3 hours. The results showed that on the fresh of meat sand sea cucumber has moisture, protein, ash, fat, and carbohydrate content was 78.94%, 79.67%, 6.74%, 4.82%, and 8.77%, respectively. The nanoparticles of collagen produced showed that different stirring time was affected by the quality characteristics of nanoparticles of sea cucumber meat collagen. The best result was obtained at 3 hours of stirring time which produced collagen nanoparticles with a yield rate of 14.33%, moisture 65.79%, ash 0.70%, protein 98.23%, pH 3.83 and particle size 950 nm.